Day 4 vs. day 12 G-CSF administration following reduced intensity peripheral blood allogeneic stem cell transplant. (June 2022) - Hatch, Rachel V.; Freyer, Craig W.; Carulli, Alison; Redline, Gretchen; Babushok, Daria V.; Frey, Noelle V.; Gill, Saar I.; Hexner, Elizabeth O.; Luger, Selina M.; Martin, Mary Ellen; McCurdy, Shannon R.; Perl, Alexander E.; et al.
Introduction: Granulocyte colony-stimulating factor (G-CSF) hastens neutrophil engraftment and reduces infections after allogeneic hematopoietic cell transplant (alloHCT), yet the optimal start date is unknown. Additionally, concurrent G-CSF and methotrexate for graft-vs-host disease (GVHD) prophylaxis may potentiate myelosuppression, and prolonged G-CSF is costly. Our institution changed from day + 4 to day + 12 G-CSF initiation following reduced intensity (RIC) alloHCT with methotrexate GVHD prophylaxis. Methods: We retrospectively compared day + 4 and day + 12 G-CSF initiation after RIC alloHCT from 2017–2021. The primary endpoint was the time to neutrophil engraftment. Secondary endpoints included length of stay (LOS) and the time to platelet engraftment as well as the incidence of infectious events, acute GVHD (aGVHD), and mucositis. Results: Thirty-two patients were included in each group with similar baseline characteristics. We observed faster neutrophil engraftment (median 12 vs. 15 days, p = 0.01) and platelet engraftment (median 13 vs. 15 days, p = 0.026) with day + 4 vs. day + 12 G-CSF initiation. Median LOS was 23 days (range, 19–32) with day + 4 initiation vs. 24 days (21–30) with day + 12 (p = 0.046). The incidence of culture-negative febrile neutropenia (p = 0.12), any grade aGVHD (p = 0.58), and grade 2-4 mucositis (p = 0.8) were similar between groups. Conclusion: Compared to day + 4, day + 12 G-CSF initiation following RIC alloHCT had a longer time to neutrophil and platelet engraftment. Day + 12 initiation also resulted in longer LOS, which while statistically significant, was potentially of limited clinical significance. These findings are hypothesis generating.